Harsh Words in Mobile Legends Online Game: Influences in Real Life - Nurdiansyah, Yogananda; Darma, Virga Putra (Language Circle: Journal of Language and Literature, 2024)
Mobile legends is an online game that is very popular among all circles, be it children, teenagers, or adults. The game is a five-on-five multiplayer game with each person using one person. In the game there is a message feature provided by the application itself with the aim of communication between players both inside and outside the game. However, the message feature is abused by many players by throwing harsh words at other players. They say these words because they feel upset and angry about the results and the performance of others. This study aims to find out whether the harsh words can affect the players in the game and in their real lives. This research uses a mixed research method, which uses a quantitative approach and a qualitative approach. Starting with a quantitative approach where researchers give questionnaire questions to respondents. Furthermore, the qualitative approach is by analyzing and identifying the answers given by respondents and identifying the situation of respondents directly. From this study, it was found how often they heard and used harsh words in the game. As well as how often they hear and use these harsh words in real life. These harsh words are enough to affect them, but they still maintain their speech in real life and in the game.